(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
يهدف البحث إلى التعرف على آراء خريجي شعبة (التخطيط والإدارة التربوية) بكلية التربية في جامعة تشرين في أهم الكفايات التي يمتلكونها من وجهة نظرهم، وكذلك التعرف إلى الفروق في آرائهم تبعاً لمتغير الجنس. اشتملت عينة البحث على (220) خريجاً وخريجة للأعوام الدراسية 2004/2005 – 2008/2009. تألفت استبانة البحث من (74) عبارة موزعة على أربعة مجالات (تقييم الحاجات، التنبؤ، اتخاذ القرار، إدارة المشروع). وتم استخدام الأساليب الإحصائية التالية: النسب المئوية، والمتوسطات الحسابية، والانحراف المعياري، واختبار (T - Test). وللحكم على صدق الاستبانة عرضت على مجموعة مؤلفة من (7) محكمين بجامعتي دمشق وتشرين. وتم التأكد من ثباتها بتطبيقها على عينة استطلاعية شملت (30) خريجاً وخريجة من خلال حساب معامل إلفا كرونباخ (Cronbach – Alpha)، والذي بلغ (0.97). بينت نتائج البحث أن توافر كفايات التخطيط التربوي، حصلت على تقدير متوسط لدى خريجي شعبة (التخطيط والإدارة التربوية) بكلية التربية في جامعة تشرين. وقد كشفت النتائج أيضاً وجود فروق دالة بين الذكور والإناث على مدى امتلاك الخريجين للكفايات التخطيطية. كما قدم البحث مقترحات منها إقامة دورات تدريبية للخريجين قبل التحاقهم بالعمل، وإجراء مزيد من البحوث حول تقويم كفايات خريجي مؤسسات التعليم العالي. The Research aims at investigating the graduates opinion Section Planning and Management Educational in Tishreen University about their Efficiencies which possesses it, and to study the difference of such attitudes according to the variable of sex. The sample included (220) graduates for the academic years 2004/2005 – 2008/2009. The research used a questionnaire that included (74) items, distributed to four areas (evaluation needs, divination, taking decision, project Management). The following statistical methods were used: frequencies, percent, means, standard deviations, T – Test. Validity of the questionnaire was established though a jury of (7) of the teaching staff of education at Damascus and Tishreen Universities. Pilot sample consisted of (30) Graduates, Reliability was established by Cronbach – Alpha Reliability at lest (0.97). The final results showed that possessing the planning efficiencies were middle rated to the Graduates, and statistically significant differences are found between male and female graduates in the degree of possession efficiencies. The Research suggestions to doing training courses before joining job, as well as carrying further researches about evaluation graduates efficiencies in higher education.